Genetic, environmental and other design issues relevant for pharmacogenetics studies - Joober, Ridha (Henry Stewart Talks, 2007)
Definition of pharmacogenetics (PGx), pharmacokinetics and pharmacodynamics, Modulation of PGx phenotypes, Genetic factors play a role in determining the variability of PGx phenotypes, Study design, Genetic epidemiology, Familial aggregation studies, Twin and adoption studies, Therapeutic response to psychotropic drugs, Pharmaco-epidemiology and PGx phenotypes, Animal models, Balancing modest epidemiological evidence against biological pertinence, Studying PGx phenotypes in relation to candidate genes, Family-based vs. case control designs, Observer effect, Sampling bias, Factors related to the subject
Archived at 2021/02/25